Evaluating The Marketing Strategy Of Trigona Honey Through SWOT Analysis: A Case Study Of Batu Ma’illong Forest Farmers Group: Evaluasi Strategi Pemasaran Madu Trigona Melalui Analisis SWOT: Studi Kasus Kelompok Tani Hutan Batu Ma’illong - Sitti Marlina; Sapinah; Ferdian (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Trigona honey is one of the non-timber forest products with high economic value and strong potential to be developed as a leading local commodity in Mamasa Regency. This study aims to analyze the marketing strategy of trigona honey produced by the Forest Farmer Group Batu Ma’illong in Taupe Village, Mamasa District, Mamasa Regency. The research employed a qualitative descriptive approach using SWOT analysis to identify internal and external factors affecting product marketing. The results showed that Forest Farmer Group Batu Ma’illong possesses several key strengths, including adequate production capacity, affordable product prices, the use of production technology, halal certification, and guaranteed product authenticity. However, the group still faces several challenges, particularly in marketing, capital, and cultivation skills. External factors indicate significant market opportunities due to increasing public interest in trigona honey, although business competition and economic conditions remain challenges. Based on the SWOT analysis, the business position falls within Quadrant I, indicating that an aggressive strategy should be implemented by leveraging strengths to seize market opportunities. Therefore, strengthening branding, expanding marketing networks, and utilizing digital media are recommended as the main strategies to enhance the competitiveness and sustainability of Forest Farmer Group Batu Ma’illong’s trigona honey business.